National Health Interview Survey, 1989: AIDS Knowledge and Attitudes Supplement ([Verlag nicht ermittelbar], 1992)
The basic purpose of the National Health Interview Survey (NHIS) is to obtain information about the amount and distribution of illness, its effects in terms of disability and chronic impairments, and the kinds of health services people receive. The 1989 AIDS Knowledge and Attitudes Supplement provides 93 variables from the core Person File (see NATIONAL HEALTH INTERVIEW SURVEY, 1989 [ICPSR 9583]) including sex, age, race, marital status, veteran status, education, income, industry and occupation codes, and limits on activity. The 166 variables unique to this supplement cover attitudes towards and knowledge of AIDS, the effects of the disease, how it is spread, where to obtain information on AIDS, detection of HIV with blood tests, how to avoid getting the disease, and personal knowledge of anyone who had the test for AIDS, tested positively for the virus, or had the disease.